Onuphis and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918 - Arias, Andrés (Zootaxa, 2016)
The taxonomy of eastern Atlantic species of the genus Onuphis has been confused due to the somewhat cursory and misleading descriptions of species and the disregard of the true identity of the type species of the genus, O. eremita, which has been commonly reported from West Africa, along with O. geophiliformis and O. rullieriana. However, all three species are now considered as unlikely to occur in western Africa. This work recognises three species of Onuphis from this region. Two of them, Onuphis augeneri sp. nov. and O. hanneloreae sp. nov., are newly described from Nyanga estuary (Gabon) and Sal Island (Cape Verde) respectively. Furthermore, Onuphis landanaensis, a species described from the Gulf of Guinea and subsequently synonymised with O. eremita, is formally reinstated and redescribed based upon the re-examination of the original types. Detailed descriptions and illustrations of all species are presented as well as the ontogenetic changes of the brooder O. hanneloreae sp. nov. Furthermore, the genus Mooreonuphis is recorded for the first time in Africa with the description of M. nunezi sp. nov. from Cape Verde archipelago. Additionally, a dichotomous key to all species of the genera Onuphis and Mooreonuphis from the eastern Atlantic is included.